2013
DOI: 10.4049/jimmunol.1201479
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of the Osteoclastogenic RANKL–RANK Axis Prevents Osteoporotic Bone Loss and Soft Tissue Calcification in Coxsackievirus B3–Infected Mice

Abstract: Bone mineralization is a normal physiological process, whereas ectopic calcification of soft tissues is a pathological process that leads to irreversible tissue damage. We have established a coxsackievirus B3 (CVB3)–infected mouse model that manifests both osteoporosis and ectopic calcification specifically in heart, pancreas, and lung. The CVB3-infected mice showed increased serum concentrations of both cytokines including IL-1β, TNF-α, and the receptor activator of NF-κB ligand (RANKL) that stimulate osteocl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…For detection of mineralization of RVSMCs, von Kossa staining was performed 53 . In brief, cells were fixed with 10% formalin for 30 min at room temperature, washed with dH 2 O three times and then incubated with 5% silver nitrate for 30 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…For detection of mineralization of RVSMCs, von Kossa staining was performed 53 . In brief, cells were fixed with 10% formalin for 30 min at room temperature, washed with dH 2 O three times and then incubated with 5% silver nitrate for 30 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…SPARC, commonly known as an indicator of bone formation, also has the ability to promote calcium deposition as well as the differentiation and survival of osteoblasts [7]. Also, SPARC represents an osteogenic marker gene, and RANKL could promote Pi-induced cardiac fibroblast calcification in vitro by activating SPARC [8]. A previous study has since demonstrated that SPARC is highly positive in ligament fibers and the periosteal membrane attached to the apex of the styloid process [9].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the up-regulation of RANKL/RANK seems to resist uremic pulp ossification and further shift the imbalance toward osteogenesis. We also speculated that the influence of RANKL/RANK pathway might be different among different tissues, which was supported by a study showing that RANKL contributes to both calcium deposition in soft tissues but calcium depletion in bone [33].…”
Section: Discussionmentioning
confidence: 92%